TINJAUAN PERANAN PBB DALAM PERKEMBANGAN PENERAPAN DAN PENGHAPUSAN HUKUMAN MATI DI DUNIA - Pudji Indah Lestari; Abdul Rahman; Chairul Bariah (Journal of USU International Law, 2013)
Abstrak The Imperfection of criminal justice system is certainty because this is a “human work”. Even in the developed country such as United State of America, the failure of criminal system – in did not punish the innocent – always occurred. Since 1973, more than 120 peoples in America who waiting the execution of death penalty are released from the penalty because there are any new evidences that they are innocent.  The appearance of international norms on the limitation and abolition of death penalty is a phenomenon in post war II. As a desires of civilized nation, the abolition is propaganda when formulate the content of Universal Declaration of Human Rights (UDHR) in 1948 although only indicated implicitly in the recognition of “right to life”. Intention to ask the abolition of death penalty is developing in international society. The abolition of the death penalty is assumed as one of important element in the development of democracy in the nations who will break down a relation to the last age with terror, injustice and oppression.  The trend of this abolition is indicated by international law product in order to encourage the abolition of death penalty. In addition to UDHR,  the other dominant law instrument of human basic right is International Covenant of Civil and Political Rights (ICCPR) and its Second Optional Protocol and any others regional conventions. In 2007, the General Assembly of United Nations (UNO) also issued a resolution “Moratorium on the Use of the Death Penalty” that ask the abolition of death penalty. International organizations implement the desires of the member nations that manifested in an international convention. Therefore, the international organization with various bonds has a closed relationship to the Nations that established the organizations and in anything always depend on the nations. UNO is universal organization in which all of Nations have right to be member. International Court ever said in the reparation for injuries case, that the Court recognizes that the establishment of UNO by majority of members in international society manifests an entity with “Objective personality”. The membership of UNO with various function had make the UNO position over than other organizations. The international law instrument that regulate about the death penalty based on UDHR as universal declaration and then to be the base of the establishment of multilateral convention (ICCRP) and three regional convention i.e. European Convention on Human Rights, American Rights) and other human basic right conventions. The issue of death penalty always associated to two norm of human basic right; a right for live and protection to the punishment or a raw deal, inhumanity and neglect the human prestige. Both of these norms can be retraced to constitutional law of Anglo American. The protection to the “cruel and usual punishment had determined in English Bill of Right in 1968, while “a right for live can not be removed without due process of law” and to take attitude “did not provide the explicit recognition to legitimating death penalty. Keywords : Peranan PBB, Penerapan dan Hukuman Mati